The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0204607
|View full text |Cite
|
Sign up to set email alerts
|

Is quality of care during childbirth consistent from admission to discharge? A qualitative study of delivery care in Uttar Pradesh, India

Abstract: BackgroundImproving quality of maternal healthcare services is key to reducing maternal mortality across developing nations, including India. Expanding access to institutionalized care alone has failed to address critical quality barriers to safe, effective, patient-centred, timely and equitable care. Multi-dimensional quality improvement focusing on Person Centred Care(PCC) has an important role in expanding utilization of maternal health services and reducing maternal mortality.MethodsNine public health faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 46 publications
6
24
0
Order By: Relevance
“…As a positive factor that both government representatives and private practitioners have expressed enthusiasm in collaborating with each other with those programmes 41 . c. Human resources A success / opportunity with availability of adequate human resources for delivery care across most public health facilities has been identi ed only in one study in India 30 . Accredited Social Health Activists (ASHAs) play a key role in facilitating the adoption of safe practices in postnatal care in India 36 .…”
Section: B Healthcare Financingmentioning
confidence: 99%
See 2 more Smart Citations
“…As a positive factor that both government representatives and private practitioners have expressed enthusiasm in collaborating with each other with those programmes 41 . c. Human resources A success / opportunity with availability of adequate human resources for delivery care across most public health facilities has been identi ed only in one study in India 30 . Accredited Social Health Activists (ASHAs) play a key role in facilitating the adoption of safe practices in postnatal care in India 36 .…”
Section: B Healthcare Financingmentioning
confidence: 99%
“…In two rural districts of Uttar Pradesh, India, process gaps are observed during delivery and post-delivery stages compromising mothers' safety and quality care 30 . Few other studies pointed out the problems with referral system for the contribution of poor quality 12,36,38,65 .…”
Section: E Leadership and Governancementioning
confidence: 99%
See 1 more Smart Citation
“…A recent (2019) study from South Africa has found inadequate discharge planning to be a significant contributor to avoidable causes of hospital readmission 13. Across India, a handful of predominantly single-site studies have evaluated and described deficiencies in information exchange during referrals, hospital shift change and discharge 14–19. The current study forms part of a series completed for a project investigating handover and continuity of care for patients with chronic NCDs in the states of Kerala and Himachal Pradesh in India.…”
Section: Introductionmentioning
confidence: 98%
“…[31] Across India, a handful of studies have found inconsistencies in the provision of discharge information via HCP and patient reports and discharge ticket evaluations. [32][33][34] In addition, a study in an Indian hospital emergency department reported improvements in recorded discharge information following the implementation of pre-formatted discharge summaries. [35] The importance of investigating factors affecting continuity of care in LMICs and India, in particular, is increasing due to the rising prevalence of chronic NCDs, which require sustained care across settings.…”
Section: Introductionmentioning
confidence: 99%